Endothelial to mesenchymal cell transition in diabetic retinopathy: targets and therapeutics - Nijim, Wasef; Moustafa, Mohamed; Humble, Julia; Al-Shabrawey, Mohamed (Frontiers in Ophthalmology, 2023)
Diabetic retinopathy (DR) is a result of neurovacular insults from hyperglycemia in diabetes mellitus (DM), and it is one of the top causes of vision loss throughout the modern world. This review article explores the role endothelial to mesenchymal transition (EndMT) has on the pathogenesis of DR. EndMT contributes to the disruption of the blood-retinal barrier, vascular leakage, neovascularization, and fibrosis observed in DR. Risk factors and biomarkers associated with DR severity are discussed, highlighting the importance of early detection and targeted therapies. Current treatments primarily focus on anti-vascular endothelial growth factor (anti-VEGF) agents, corticosteroids, and laser photocoagulation. However, emerging therapeutic strategies aimed at inhibiting EndMT and its downstream effects show promise in preventing the development and progression of DR. Understanding the molecular and cellar mechanisms underlying EndMT in DR provides valuable insights into the disease process and offers potential options for the development of potential treatments.